THE CORRELATION OF MATHEMATICAL LOGIC INTELLIGENCE AND LEARNING DISCIPLINE WITH THE ABILITY OF MATHEMATICAL CONCEPTUAL UNDERSTANDING IN DIFFERENTIATION LEARNING OF CLASS IV STUDENTS - Rani Pratiwi; Rosmaiyadi Rosmaiyadi; Sumarli Sumarli (Universitas Majalengka, 2024)
This research aims to describe the relationship between mathematical logic intelligence and learning discipline with the ability to understand mathematical concepts and determine the achievement of KKM in the ability to understand mathematical concepts in differentiated learning. This research method is correlation research with a quantitative approach. The results of the research show that (1) There is a relationship between mathematical logic intelligence and students' ability to understand mathematical concepts. The results show that the Pearson product moment correlation coefficient is 0.736 which is in the strong relationship category and the determinant coefficient is 54.16%; (2) There is a relationship between learning discipline and students' ability to understand mathematical concepts, obtained by the Pearson product moment correlation coefficient of 0.661 which is in the strong relationship category and the determinant coefficient is 43.69%; (3) There is a relationship between mathematical logic intelligence and learning discipline and students' ability to understand mathematical concepts, resulting in a multiple correlation coefficient of 0.786 which is in the strong relationship category and a determinant coefficient of 61.77%; (4) From the results of data calculations, students' ability to understand mathematical concepts has the coefficient results of one sample t-test with Asymp. Sig (2-tailed) = 0.001, then 0.001 < 0.05 so it can be concluded that the ability to understand concepts with differentiated learning can help class IV A students at SDN 27 Singkawang achieve the minimum completeness criteria (KKM).